THE NEED TO DEVELOP HUMAN CAPITAL IN THE DIGITAL ECONOMY - Ganiev I. M.; Xoshimova S.B. (Galaxy International Interdisciplinary Research Journal, 2023)
In the conditions of the digital economy, human capital is becoming one of the most important factors of economic growth and economic development. The world is becoming increasingly digitized, which increases the need for skilled workers who can handle, maintain, and innovate with digital tools and technologies. In this article, we explore the role of human capital in the digital economy and why investing in human capital is important.